Chemo-dynamics and asteroseismic ages of seven metal-poor red giants from the Kepler field. Issue 2 (8th December 2021) - Alencastro Puls, Arthur; Casagrande, Luca; Monty, Stephanie; Yong, David; Liu, Fan; Stello, Dennis; Aguirre Børsen-Koch, Victor; Freeman, Ken C
ABSTRACT: In this work, we combine information from solar-like oscillations, high-resolution spectroscopy, and Gaia astrometry to derive stellar ages, chemical abundances, and kinematics for a group of seven metal-poor red giants and characterize them in a multidimensional chrono-chemo-dynamical space. Chemical abundance ratios were derived through classical spectroscopic analysis employing 1D LTE atmospheres on Keck/HIRES spectra. Stellar ages, masses, and radii were calculated with grid-based modelling, taking advantage of availability of asteroseismic information from Kepler. The dynamical properties were determined with galpy using Gaia EDR3 astrometric solutions. Our results suggest that underestimated parallax errors make the effect of Gaia parallaxes more important than different choices of model grid or – in the case of stars ascending the red giant branch – mass-loss prescription. Two of the stars in this study are identified as potentially evolved halo blue stragglers. Four objects are likely members of the accreted Milky Way halo, and their possible relationship with known accretion events is discussed.